PENERAPAN POLA GERAK DOMINAN BERBASIS KESEIMBANGAN DAN TUMPUAN UNTUK MENINGKATKAN HASIL BELAJAR AKTIVITAS SENAM LANTAI - Siti Annisa Nurhikmah, - (2019)
The purpose of this study was to improve the learning outcomes of floor gymnastics activities in grade II C students of SD Negeri 053 Cisitu, Coblong Subdistrict, Bandung in the academic year 2019/2020 by applying the Dominant Motion Pattern (PGD) approach based on balance and pedestal. This research is a classroom action research (CAR). Data sources come from teachers and students. Data collection techniques are by testing and observation. Data analysis using descriptive techniques using percentage techniques to see trends that occur in the learning process. The results showed that through the Dominant Motion Pattern approach (PGD) could improve the learning outcomes of floor gymnastics in grade II C students of SD Negeri 053 Cisitu, Coblong Subdistrict, Bandung City in 2019/2020. From the results of the analysis of the application of the Dominant Motion Pattern approach (PGD) in the learning activities of class II C floor gymnastics activities at SD Negeri 053 Cisitu Bandung increased learning outcomes in balance movements by 17.2% from initial observation to cycle 1 and by 65% from cycle 1 to cycle 2. While for pedestrian movements, it results in 19.3% from initial observations to cycle 1 and 38% from cycle 1 to cycle 2. From this result, it means that by applying the Dominant Motion Pattern (PGD) approach it can improve learning outcomes in activities floor gymnastics significantly. The conclusion of this research is the application of the dominant motion pattern approach based on balance and pedestal can improve the learning outcomes of floor gymnastics in class II C of Public Elementary School 053 Cisitu, Coblong Subdistrict, Bandung in the academic year 2019/2020. Keywords: dominant motion pattern approach, balance and pedestal, learning outcomes